Calidad de vida y desarrollo del estrés de un adulto mayor de 80 años de edad de la Parroquia Febres Cordero - Nuñez Yungan, Joselyn Stefania (2023)
Research in the field of health and well-being of the elderly population is of utmost importance today, as the aging of the population is a global trend that presents significant challenges for society. The case study focuses on the quality of life and the development of stress in an elderly person over 80 years old, residing in the Parish of Febres Cordero. An integrated approach is used, including a conceptual framework, medical history, and various psychometric assessments, with a particular emphasis on the Coping Inventory for Stressful Situations. This study provides a detailed understanding of the situation of this elderly individual in terms of their quality of life and their ability to cope with stress. Areas of concern were identified, such as physical health, social relationships, autonomy, and stress coping. Through the application of the COPE Inventory, the coping strategies used by the individual to deal with stressful situations were analyzed. These results served as the basis for the development of a specific therapeutic plan that addressed the unique needs and challenges of this elderly person.